JURIDICAL ANALYSIS OF CONSUMER PROTECTION FOR PASSENGERS AS SEXUAL HARASSMENT VICTIMS BY DRIVERS OF ONLINE TRANSPORTATION SERVICE COMPANIES (COMPARATIVE STUDY BETWEEN INDONESIAN LAW WITH CALIFORNIA LAW) - Akbar, Zulfiandi Putranda; Sutanti, Rahmi Dwi; Irawati, Irawati (Diponegoro Law Journal, 2023)
The rapid growth of online transportation service companies has revolutionized the way people commute, providing convenience and accessibility. However, alongside this progress, there has been an alarming rise in reported cases of sexual harassment experienced by passengers at the hands of drivers. This research investigates the pressing issue of sexual harassment within the context of online transportation services, focusing on the jurisdictions of Indonesia and California. As the issue of sexual harassment in the online transportation industry continues to be a significant concern, this research aims to contribute to the ongoing discourse surrounding consumer protection and passenger safety. By identifying the strengths and weaknesses of the legal frameworks, the study proposes recommendations for enhancing protections against sexual harassment and promoting a safer and more inclusive environment for passengers. The research goes beyond the legal aspects and examines the impact of sexual harassment on passengers’ well-being and confidence in utilizing online transportation services. By applying on the legal enforcement of both jurisdiction and each company’s policies, the study sheds light on the prevalent patterns of sexual harassment and the responses of online transportation service companies in addressing these issues